Developing a Molecular Mathematical Model for the Dissemination of Dengue Fever Incorporating Human Mobility Variables - Andri Rahadyan (Journal of Innovative and Creativity, 2025)
In 2009, the World Health Organisation disclosed that Indonesia has the highest frequency of dengue fever in Southeast Asia. In 2014, the Ministry of Health of the Republic of Indonesia publicly disclosed that a substantial number of dengue fever cases were recorded across all regions of Indonesia. Spatial heterogeneity and human mobility are the principal variables that complicate dengue transmission. This work centres on developing a genetic model for dengue disease transmission, incorporating human movement between two distinct clusters. The molecular model addresses both human mobility and spatial heterogeneity. In this specific molecular model, each individual person and female Aedes aegypti mosquito is designated as a particle, but the collective population of humans and mosquitoes is termed a particle system. This molecular model consists of three different phases. Their coverage includes factors such as population growth dynamics, alterations in regional distribution, and fluctuations in infection status among humans and mosquitoes. The dynamics influence the interactions between humans and mosquitoes. Simulations have been carried out with a variety of contact radii and human motion patterns taken into consideration. The simulation results indicate that the intensity of dengue transmission escalates with heightened human mobility and an expanded interaction radius during disease propagation.